Tokopedia Paylater's Influence on Impulsive Purchases - Idris, Norhalimas; Lee, Yong-Ki (Journal of Management, 2022)
The Effect of Using Tokopedia Paylater on Impulsive Purchases among Students of the Faculty of Psychology, University of Padjadjaran is the title of this study. The goal of this study was to see how Tokopedia paylater affected the purchasing habits of students at the University of Padjadjaran's Faculty of Psychology. This is a quantitative study that takes a descriptive method. The population in this study consisted of 2500 current students from the Faculty of Psychology, whereas the sample consisted of 111 students. According to SPSS analyses, the coefficient of determination for TokopediaPay has a substantial effect on impulsive purchases of 42.7%. The remaining 57.8% is due to the influence of other factors not investigated in this study.